Mapping of multiple neurotransmitter receptor subtypes and distinct protein complexes to the connectome. - Sanfilippo, P.; Kim, A.J.; Bhukel, A.; Yoo, J.; Mirshahidi, P.S.; Pandey, V.; Bevir, H.; Yuen, A.; Mirshahidi, P.S.; Guo, P.; Li, H.S.; Wohlschlegel, J.A.; et al. (Neuron, 2024)
Neurons express various combinations of neurotransmitter receptor (NR) subunits and receive inputs from multiple neuron types expressing different neurotransmitters. Localizing NR subunits to specific synaptic inputs has been challenging. Here, we use epitope-tagged endogenous NR subunits, expansion light-sheet microscopy, and electron microscopy (EM) connectomics to molecularly characterize synapses in Drosophila. We show that in directionally selective motion-sensitive neurons, different multiple NRs elaborated a highly stereotyped molecular topography with NR localized to specific domains receiving cell-type-specific inputs. Developmental studies suggested that NRs or complexes of them with other membrane proteins determine patterns of synaptic inputs. In support of this model, we identify a transmembrane protein selectively associated with a subset of spatially restricted synapses and demonstrate its requirement for synapse formation through genetic analysis. We propose that mechanisms that regulate the precise spatial distribution of NRs provide a molecular cartography specifying the patterns of synaptic connections onto dendrites.